METAMORPHIC EVOLUTION OF GARNET–BIOTITE–MUSCOVITE SCHIST FROM BARRU COMPLEX IN SOUTH SULAWESI, INDONESIA - Nugroho Imam Setiawan; Yasuhito Osanai; Nobuhiko Nakano; Tatsuro Adachi (Journal of Applied Geology, 2015)
This paper explains the first report in metamorphic evolution of pelitic schist from Barru Complex in South Sulawesi, Indonesia. Garnet-biotitemuscovite schist was examined petrologically to assess the metamorphic evolution history, which has implications on tectonic condition of this region. The rock mainly composed of garnet, biotite, muscovite, epidote, quartz, rutile, hematite, and plagioclase. Inclusions in the garnet preserve records of prograde stage of this rock, which are epidote, titanite, quartz, and apatite. Garnet, biotite, muscovite, quartz, rutile, and plagioclase are concluded as equilibrium assemblages at peak P-T condition of this rock, which estimated at 501–562 ºC and 0.89–0.97 GPa. The result is still on the ranges of the estimated geothermal gradient P-T path of eclogite from Bantimala Complex. Similar geothermal gradients of metamorphisms might be indicated that these metamorphic rocks were metamorphosed on the similar tectonic environments. Keywords: Pelitic schist, Barru Complex, South Sulawesi, metamorphic evolution.